2004
DOI: 10.1152/ajprenal.00065.2004
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II directly stimulates activity and alters the phosphorylation of Na-K-ATPase in rat proximal tubule with a rapid time course

Abstract: We present evidence that Na-K-ATPase in the rat proximal tubule is directly activated by ANG II much faster than previously observed. Specifically, we show that a 2-min exposure to 0.1 and 1 nM ANG II slowed the rate of intracellular sodium accumulation in response to an increase in extracellular sodium added in the presence of gramicidin D. From these data, we show that ANG II directly stimulates Na-K-ATPase activity at rate-limiting concentrations of intracellular sodium. Under these same conditions, exposin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 47 publications
1
30
0
1
Order By: Relevance
“…There are no previous reports in the literature to our knowledge showing the effects of chronic ANG II infusion on Na pump activity by this segment; however, there is one study showing that at longer infusion times Na pump expression decreases in the ISOM (44). Our results are consistent with studies in the proximal tubule that show that acutely ANG II stimulates Na pump activity (18,66). They are also consistent with studies showing that chronic elevations of ANG II enhance Na pump activity in other tissues (20,26).…”
Section: Discussionsupporting
confidence: 91%
“…There are no previous reports in the literature to our knowledge showing the effects of chronic ANG II infusion on Na pump activity by this segment; however, there is one study showing that at longer infusion times Na pump expression decreases in the ISOM (44). Our results are consistent with studies in the proximal tubule that show that acutely ANG II stimulates Na pump activity (18,66). They are also consistent with studies showing that chronic elevations of ANG II enhance Na pump activity in other tissues (20,26).…”
Section: Discussionsupporting
confidence: 91%
“…The [K] pip dependence is consistent with an effect of ANG II to accelerate the backward E 1 ϩ 2K ϩ 3 E 2 (K ϩ ) 2 reaction (5). ANG II increases Na ϩ -K ϩ -ATPase activity and enhances phosphorylation of peptide fragments cleaved from the intact enzyme in rat proximal renal tubule (42). However, the effects of PKCmediated phosphorylation of the Na ϩ -K ϩ pump are varied and tissue specific.…”
Section: Discussionmentioning
confidence: 99%
“…Many humoral factors, high salt intake, or hormones regulate proximal tubular sodium transport at least in part by altering the expression and activity of Na + -K + -ATPase or by inducing the endocytosis of Na + -K + -ATPase into proximal tubule cells (95; 132; 324). For example, Yingst et al demonstrated that the vasoactive peptide angiotensin II (ANG II) directly stimulates the activity and alters the phosphorylation of Na + -K + -ATPase in rat proximal tubules with a rapid time course (561; 562). Similar effects of ANG II on Na + -K + -ATPase activity were reported in proximal tubule cells or proximal straight tubules in vitro (126; 152).…”
Section: Physiological Regulation Of Proximal Tubule Functionsmentioning
confidence: 99%